THE FOUNDATION OF DEVELOPING CHARACTER BUILDING IN HAMZANWADI NAHDHADUL WATHAN DINIYAH ISLAMIYAH (NWDI) ISLAMIC BOARDING SCHOOL IN EAST LOMBOK - Badrun, Badrun (Universitas Islam Negeri Mataram, 2022)
The issues of character-building quality and morality in Indonesia still become everyday tasks. A high rate of crime and violence occurs in ordinary people's life. Many younger generations, particularly school-age kids, were engaged in promiscuity, brawls, fight, et cetera. Thus, for solving the youth generation problem from an early age, improving character building is necessary. Islamic boarding school has a very strategic role in building character. The study is qualitative research with a study case in Hamzanwadi Nahdhadul Wathan Diniyah Islamiyah (NWDI) Islamic boarding school through an interview, thorough discussion, and direct observation in the research site. The study shows that the foundations for developing character building are religious, philosophical, and empirical. These three foundations make Hamzanwadi Diniyah Islamiyah (NWDI) Pancor Islamic boarding school still exists and become exemplary for other Islamic boarding schools in developing character building. The character built corresponds to the expectation of the Islamic boarding school founder